Perilaku Impulsive Buying: Implementasi Pendekatan Technology Acceptance Model Pada Keputusan Pembelian E-commerce - Puteri Anindya Maulan; Ivan Permana; Jentoro Wicaksono; Edwin Zusrony; Agustinus Budi Santoso (Jurnal Informatika Ekonomi Bisnis, 2024)
The behavior of purchasing products via e-commerce is quite often carried out by Gen Z who are attracted by discount promos and are tempted by cheap prices. This research aims to determine the influence of impulsive buying and technology acceptance model (TAM) through the trust variable on product purchasing decisions in e-commerce by Gen Z. This research is a quantitative research with associative methods using primary data with a sample of 100 respondents from all final year students in the city of Semarang. The sampling technique uses a non-probability sampling technique with a purposive sampling method. The data collection technique uses a questionnaire with a Likert scale. The data analysis technique uses SEM-PLS and is processed using SmartPLS 4.0 software. The results of data analysis show that five hypotheses were tested, four hypotheses were accepted and one hypothesis was rejected. The impulsive buying and technology acceptance model variables have a significant effect on the trust variable, while the trust variable also has a significant effect on purchasing decisions. Then the technology acceptance model variable has no influence at all on the trust variable, so the fourth hypothesis is rejected.